3D geometry analysis of the medial meniscus – a statistical shape modeling approach. Issue 4 (23rd July 2014) - Vrancken, A. C. T.; Crijns, S. P. M.; Ploegmakers, M. J. M.; O'Kane, C.; van Tienen, T. G.; Janssen, D.; Buma, P.; Verdonschot, N.
Abstract The geometry‐dependent functioning of the meniscus indicates that detailed knowledge on 3D meniscus geometry and its inter‐subject variation is essential to design well functioning anatomically shaped meniscus replacements. Therefore, the aim of this study was to quantify 3D meniscus geometry and to determine whether variation in medial meniscus geometry is size‐ or shape‐driven. Also we performed a cluster analysis to identify distinct morphological groups of medial menisci and assessed whether meniscal geometry is gender‐dependent. A statistical shape model was created, containing the meniscus geometries of 35 subjects (20 females, 15 males) that were obtained from MR images. A principal component analysis was performed to determine the most important modes of geometry variation and the characteristic changes per principal component were evaluated. Each meniscus from the original dataset was then reconstructed as a linear combination of principal components. This allowed the comparison of male and female menisci, and a cluster analysis to determine distinct morphological meniscus groups. Of the variation in medial meniscus geometry, 53.8% was found to be due to primarily size‐related differences and 29.6% due to shape differences. Shape changes were most prominent in the cross‐sectional plane, rather than in the transverse plane. Significant differences between male and female menisci were only found for principal component 1, which predominantly reflected size differences. The cluster analysis resulted in four clusters, yet these clusters represented two statistically different meniscal shapes, as differences between cluster 1, 2 and 4 were only present for principal component 1. This study illustrates that differences in meniscal geometry cannot be explained by scaling only, but that different meniscal shapes can be distinguished. Functional analysis, e.g. through finite element modeling, is required to assess whether these distinct shapes actually influence the biomechanical performance of the meniscus.